1909 Vol. IX, No. 1, June 1909, Bulletin of the First District Normal School, Kirksville, Missouri - First District Normal School (Kirksville, Mo.) (publisher not identified, 1909)
This is a digital copy of the bulletin containing courses of study, syllabi, and faculty for the 1909-10 academic year, as well as lists of students and alumni.